BIOACCUMULATION AND BIOMAGNIFICATION OF MERCURY AND SELENIUM IN THE SARASOTA BAY ECOSYSTEM. (29th March 2013) - Hong, Yong‐Seok; Hull, Peter; Rifkin, Erik; Bouwer, Edward J.
Abstract The bioaccumulation and biomagnification of Hg and Se were investigated in Sarasota Bay, Florida, USA, to characterize the Hg exposure risks to wild bottlenose dolphins in the bay. Concentrations of total mercury (THg), monomethylmercury (MMHg), and total selenium (TSe) were monitored in the bay, the latter of which might reduce Hg toxicity. The food web structure and dolphins' trophic level–specific consumption rates were evaluated using stable isotope ratios of carbon (δ13C) and nitrogen (δ15N). Regressions developed for Hg biomagnification in the food chain were log10CTHg (nanograms per gram) = 0.27 × δ15N (‰) – 0.42, R2 = 0.87, for THg and log10CMMHg = 0.33 × δ15N (‰) – 1.0, R2 = 0.93, for MMHg. Unlike Hg, nearly constant TSe concentrations were observed at 248 ± 179 ng g−1 in the food web, and the TSe‐to‐THg molar ratio was predicted by log10(CTSe/CTHg) = −0.10 × δ15N (‰) + 2.8, R2 = 0.60. The THg‐uptake rates of Sarasota bottlenose dolphins are estimated to vary between 2.1 and 4.9 µg kg−1 d−1; however, the estimated TSe‐uptake rates (15.1 µg kg−1 d−1) were higher than those for THg, and the Hg‐exposure risks of the Sarasota Bay resident bottlenose dolphins are considered to be low. Approaches employed in the present study can be extended to other environments to characterize Hg contamination in aquatic systems and Hg exposure risks in top predators. Environ. Toxicol. Chem. 2013;32:1143–1152. © 2013 SETAC